EFEKTIVITAS METODE INQUIRY TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Kusumaningtyas, Wahyu (JURNAL E-DUMATH, 2016)
Learning model applied by the teacher guessed not create a learningatmosphere that involve the students optimally. One of the efforts to solvethe problem is use inquiry method, because this method involves thestudents actively and creatively. This study aims to know theeffectiveness of inquiry learning method in the third grade SMP IT AlMunir Sukoharjo on the circle material. The population of this study isall of the third grade students in the even semester SMP IT Al MunirSukoharjo in the academic year 2014-2015 total 230 students. Based onthe findings, it concluded that inquiry method is effective for learningactivity seen from the process and students learning outcome in circlematerial seen from the process include the teacher capability in learningprocess is 76%, students activity is 75%, students response is 77,17%and if seen from learning outcome that achieve Minimum CompletenessCriteria classically is 81,25%.Keywords: inquiry learning method, effectiveness learning model